Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Pakan Ternak Ayam Pedaging di Kabupaten Jombang Jawa Timur - Hotman Panjaitan; Herry Cahyanto (Universitas 17 Agustus 1945 Surabaya, 2017)
Livestock activity is one of the sub activities in agriculture, where with the increase ofthe welfare of the community, the activities in the field of livestock are also increasing as aconsequence of the increase of people's income. Meat as one source of protein is needed bythe community, while chicken meat is still a prima donna community in meeting the needsof meat because in addition to the relatively cheap price, good taste, also from the aspectof relative health does not contain lots of cholesterol, therefore Animal feed company, iscurrently racing to market its production. Marketing mix as attribute inherent to a product that is used as consumer appeal, sothat marketing mix must be communicated well to consumer through various media ofinformation to influence consumer. The impact for consumer marketing mix informationwill be a stimulus in making the decision to buy. From the results of the test of the model in this study, using random sampling,structural equation model (SEM) analysis, and software assistance Amos Version 22, in201 respondents, able to explain the relationship between marketing mix (product, price,promotion and distribution) Purchase of livestock feed, in the area of Jombang regency.In this study, obtained value of Coefficient of Determination (R2) of 0.816, this indicatesthat, by executing the marketing mix well, it will push upthe decision of livestock feedpurchase of 81.6%. Another thing to be gained from is: that the promotion factor of the marketing mixbecomes the most dominant factor influence on purchasing decisions, amounting to 44.8%.Keywords: marketing mix, purchase decision